Case Report: Transthyretin Glu54Leu—a rare mutation with predominant cardiac phenotype - Gospodinova, Mariana; Zhelyazkova, Sashka; Chamova, Teodora; Asenov, Ognyan; Pavlova, Zornitsa; Todorov, Tihomir; Mikova, Dilyana; Palashev, Yordan; Gruev, Ivan; Kundurdjiev, Atanas; Todorova, Albena; Tournev, Ivailo (Frontiers in Cardiovascular Medicine, 2023)
We report two unrelated Bulgarian families with hereditary transthyretin (ATTR) amyloidosis due to a rare p.Glu74Leu (Glu54Leu) pathogenic variant found in seven individuals—three of them symptomatic. Only one family with the same variant and with a Swedish origin has been clinically described so far. Our patients are characterized by predominant cardiac involvement, very much similar to the Swedish patients. Although the initial complaint was bilateral carpal tunnel syndrome, advanced amyloid cardiomyopathy was found in two symptomatic carriers at diagnosis with heart failure manifestations. The neurological involvement was considered as mild, with mainly sensory signs and symptoms being present. We followed a non-biopsy algorithm to confirm the diagnosis. Tafamidis 61 mg has been initiated as the only approved disease modifying treatment for ATTR cardiomyopathy. Clinical stability in the absence of adverse events has been observed at follow up.